Development and Validation of E-Comic-Based Interactive Learning Media for Elementary Education - Khairunnisak, Khairunnisak; Sumanti, Sumanti; Muharramsyah, Rambang (International Journal of Educational Dynamics, 2024)
This study aims to develop interactive learning media with an economic basis and assess its validity and reliability. Using a developmental study approach or Research and Development (R&D) with the ADDIE framework (Analysis, Design, Development, Implementation, and Evaluation), the study focuses on designing and validating e-comic-based learning media for elementary students. Data collection methods included observations, interviews with teachers and principals, documentation, and triangulation. The analysis employed both qualitative and quantitative techniques using SPSS version 29.0. The findings reveal that the e-comic learning media and its usage guidebook are valid and reliable. The e-comic achieved an average validity score of 4.129 (84%) with a Cronbach's alpha of 0.96, reflecting high inter-rater agreement. Similarly, the guidebook scored an average validity of 3.72 (83%) with a Cronbach's alpha of 0.90, demonstrating excellent reliability. These tools address students' low interest in traditional learning methods by offering an engaging and accessible medium aligned with curriculum standards. The media fosters critical thinking, literacy, and problem-solving skills while reducing students' reliance on gadgets for non-educational purposes. his study highlights the potential of e-comic media as an innovative solution for enhancing elementary education. Further study is recommended to explore its adaptability to other subjects and its long-term effects on learning outcomes.